CORPORATE SOCIAL RESPONSIBILITY – ONE STEP FURTHER TOWARDS SUSTAINABLE DEVELOPMENT - BOGHEAN, Florin (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The development of this paper has been based on an approach that moves from the international to the national sphere, with particular focus on the aspects concerning social responsibility, a component of efficient corporate governance, starting from the idea that a summary of the findings of these comparative studies is essential, as they may become actual examples of practical use of the various corporate governance theories, with the possibility to highlight the best practices of corporate governance in general. The range of benefits such a research project conveys also includes the possibility to identify and understand the international best practices in the CSR field that would further contribute to the implementation of the corporate governance principles and the further enhancement of CSR for Romanian business entities.